2021
DOI: 10.3390/app112411699
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Semantic Consistency for Multilingual Sentence Representation Using an Explainable Machine Natural Language Parser (MParser)

Abstract: In multilingual semantic representation, the interaction between humans and computers faces the challenge of understanding meaning or semantics, which causes ambiguity and inconsistency in heterogeneous information. This paper proposes a Machine Natural Language Parser (MParser) to address the semantic interoperability problem between users and computers. By leveraging a semantic input method for sharing common atomic concepts, MParser represents any simple English sentence as a bag of unique and universal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The results of the study is different from the research (Longo, 2022) grammar can improve the application of formal language, (Siregar, 2020) analyzed the level and size of English vocabulary, but does not clearly discuss the grammar of the case which is the theme of the study, (Qin et al, 2021) stated a common semantic representation for multilingual languages is an essential goal of the NLP community. To facilitate multilingual sentence representation and semantic interoperability, this study presented an MParser for parsing local language sentences and providing a common understanding across the heterogenic sentence, (Zhang, L., & Su, 2021) elaborated a local grammar approach to diachronic studies of discourse acts in academic texts and demonstrated the approach with a case study investigating diachronically exemplification in Linguistics study articles, (Dong, Y., & Shi, 2021;McCarthy, K. S., Roscoe, R. D., Allen, L. K., Likens, A. D., & McNamara, 2022) elaborated grammarly application to support students sourcebased writing practices and writing evaluation, provided plagiarism alerts but also help students with their source use practices and can be used as an effective tool to facilitate students' learning and assessment of source-based writing, demonstrated strategy feedback with an opportunity to revise contributed to improved essay quality, but that spelling and grammar feedback provided modest, complementary benefits.…”
Section: Propositionmentioning
confidence: 76%
See 2 more Smart Citations
“…The results of the study is different from the research (Longo, 2022) grammar can improve the application of formal language, (Siregar, 2020) analyzed the level and size of English vocabulary, but does not clearly discuss the grammar of the case which is the theme of the study, (Qin et al, 2021) stated a common semantic representation for multilingual languages is an essential goal of the NLP community. To facilitate multilingual sentence representation and semantic interoperability, this study presented an MParser for parsing local language sentences and providing a common understanding across the heterogenic sentence, (Zhang, L., & Su, 2021) elaborated a local grammar approach to diachronic studies of discourse acts in academic texts and demonstrated the approach with a case study investigating diachronically exemplification in Linguistics study articles, (Dong, Y., & Shi, 2021;McCarthy, K. S., Roscoe, R. D., Allen, L. K., Likens, A. D., & McNamara, 2022) elaborated grammarly application to support students sourcebased writing practices and writing evaluation, provided plagiarism alerts but also help students with their source use practices and can be used as an effective tool to facilitate students' learning and assessment of source-based writing, demonstrated strategy feedback with an opportunity to revise contributed to improved essay quality, but that spelling and grammar feedback provided modest, complementary benefits.…”
Section: Propositionmentioning
confidence: 76%
“…This study is urgently needed in case grammar studies due to the lack of these studies in recent years (after 1970s). In the last three years, there are several studies have discussed grammar including shape grammars (Eilouti, 2019), shape grammar and block morphological analysis (Wang et al, 2020), the level and size of the vocabulary (Siregar, 2020), fusion grammars (Lye, 2022b), grammar attribute (Kramer et al, 2021), catogorial grammars (Kuhlmann et al, 2022), context-free grammar (Chen, W. Y., & Fu, 2022), formal grammars (Albarracín-Molina et al, 2021), case grammar (Basid, Abdul & Maghfiroh, 2021;Basid et al, , 2023Basid & Zahroh, 2022), English grammar (Nikiforidou, 2021), domain knowledge in grammar (Brence et al, 2023), propositions as discourse marker (Harb et al, 2022), grammar can improve the application of formal language (Longo, 2022), multiplicity in grammar (Matsumoto & Iwasaki, 2022), grammar construction (Qin et al, 2021), structural grammar (Tomei et al, 2022), local grammars (Zhang, L., & Su, 2021), writing practices (Dong, & Shi, 2021), writing evaluation (McCarthy, K. S., Roscoe, R. D., Allen, L. K., Likens, A. D., & McNamara, 2022), grammar and genre (Fischer & Asrestrup, 2021), grammatical variability (Matsumoto, 2021), grammar context (Mrykhin & Okhotin, 2023), the case of contrastive connectives (Cuenca, 2022), and nasal harmony and word-internal language mixing (Russell, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explainability is a matter of study which is gaining deserved interest in recent years, in order to guarantee trustworthy systems. The work presented in [22] proposes a system to represent multilingual sentences using a natural machine language. The paper generates related universal concepts that are intuitive, according to human evaluation.…”
Section: Other Tasksmentioning
confidence: 99%
“…Some research studies have focused on improving or explaining the robustness of the quality assurance system, such as iterative input [49] to improve the quality of the text summarization system, and the combination of decision trees and enhancement techniques [50] to improve the classification accuracy. Qin et al [51] proposed a Machine Natural Language Parser (MParser) to address the semantic interoperability problem between users and computers. To evaluate the annotator agreement of MParser outputs, 154 non-expert participants manually evaluated the sentences' semantic expressiveness.…”
Section: Related Workmentioning
confidence: 99%